Characterization of Arthrospira platensis cultured in wastewater of Clarias catfish farming media: DNA barcode, helical form, growth, and phycocyanin - Marini Wijayanti; Mochamad Syaifudin; Yulisman Yulisman; Yully Nurianti; Anita Hidayani; Nuni Gofar (Society for Indonesian Biodiversity, 2020)
Abstract. Wijayanti M, Syafudin M, Yulisman, Nurianti Y, Hidayani A, Gofar N. 2020. Characterization of Arthrospira platensis cultured in wastewater of Clarias catfish farming media: DNA barcode, helical form, growth, and phycocyanin. Biodiversitas 21: 5872-5883. Arthrospira production technology in catfish waste media can be an alternative to reduce environmental pollution. However, some environmental factors such as nutrition, light, and water content can influence characterization of Arthrospira at the genetic and physiologic level. Arthrospira platensis is one of the phycocyanin-producing cyanobacteria and can be cultured using catfish culture wastewater. Water quality especially pH and salinity can effect of growth rate and residue of phycocyanin from Arthrospira platensis. This study aimed to identify the species and morphological forms of Arthrospira cultured using technical fertilizer and waste media, as well as to know the phylogenetic trees between species in this study and the GeneBank based on the 16S rRNA gene, and determine the optimum of pH and salinity required in the medium of catfish culture wastewater to phycocyanin maximum production of Arthrospira. The optimation of pH and salinity method used Completely Randomized Design (CRD) factorial with 2 factors consisting of the first factor with 3 treatments and the second factor with 4 treatments and 3 replications. The first factor was pH of culture medium i.e. pH 6.5 ± 0.2, pH 8.5 ± 0.2 and pH 10.5 ± 0.2. The second factor was salinity of culture medium, that was salinity 0 ppt (parts per thousand/‰), 10 ppt, 20 ppt, and 30 ppt. Parameters observed in Arthrospira include density, growth rate, rendement of phycocyanin, and decreased total nitrogen and phosphate content in culture media. The results showed that morphology Arthrospira cultured on technical fertilizer media (AF) had a longer and helix filament compared to Arthrospira cultured on waste media (AW) which showed several linear and shorter filaments. Both samples have a genetic distance of 0.068 (6.8%). Phylogenetic trees indicated that AF had a close relationship with Arthrospira platensis petH from Japan (bootstrap value 95%). While AW formed a separate sub-cluster of AF isolates and Arthrospira platensis petH from Japan (bootstrap value of 85%). The best treatment in this study was P2S3 (pH 8.5 ± 0.2 with salinity 20 ppt), which produced 0.867 grams maximum density, growth rate of 22.026 %.day-1 and 11.347 mg.g1 rendement of phycocyanin.